Fonclaire is People's Top Steelband - Unknown (Sunday Express)
According to the People's Choice, the champion steelband for 1971 is Mosco Tiles Fonclaire of San Fernando. The steelband was the only one from South to make the Panorama finals.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago